Can scleroderma be induced by anesthetics? Case report - Nicola Magnavita (Nofer Institute of Occupational Medicine, 2016)
Occupational exposure to solvents is consistently associated with the risk of systemic sclerosis. We pose the question of whether the occupational exposure to anesthetics may favor the occurrence of this disease. This paper describes an incidence of systemic sclerosis in the case of an anesthesiologist who had been occupationally exposed to high doses of anesthetic in the operating room. Anecdotal cases in the literature give limited support to the causal association of the occupational exposure to anesthetics and systemic sclerosis. The extremely limited number of workers exposed makes it necessary to report all cases observed in order to assess the degree of the occupational risk for anesthesiologists. Med Pr 2016;67(4):557-560